Keski-ikäisten naisten lantionpohjan toimintahäiriöiden yhteys mielialaan - Tikka, Aino (2024)
Pelvic floor dysfunctions are quite common among women, and the risk of dysfunction may increase with age and hormonal changes associated with menopause. Pelvic floor dysfunctions have been found to be associated with, for example, decreased quality of life, increased depressive symptoms, and social isolation. The purpose of this master's thesis was to investigate the relationship between pelvic floor dysfunctions and mood in middle-aged women.